Sediment Characteristics and Impacts at Tugu Dam, Trenggalek, East Java - Fajar Fadillah; Minarni Nur Trilita; Novie Handajani (UPN Veteran Jatim, 2026)
Dam infrastructure plays a crucial role in the development and management of water resources. The Tugu Dam was constructed in 2014 and completed in 2021. High erosion rates in the Tugu Dam watershed area are a primary factor contributing to sedimentation within the reservoir. It is inevitable that river inflows carry sediment loads into the dam, which subsequently settle and cause reservoir siltation. This sedimentation-induced reduction in storage capacity can significantly impact the operational performance of the Tugu Dam. The objective of this final project is to determine the amount of sedimentation deposited, analyze the sedimentation patterns, and learn how to perform sediment modeling using the HEC-RAS application. This study employs HEC-RAS version 6.0, a software developed by the US Army Corps of Engineers, widely used for hydrologic analyses including river flow, flood modeling, dam breach simulations, and sediment transport analysis. The data utilized are secondary data obtained from the Brantas River Basin Organization (BBWS Brantas). Based on the calculations and analyses conducted in this study, sediment transport modeling requires three primary data inputs: geometric data, hydrologic data, and sediment data. The modeling results indicate a decrease in dead storage capacity from an initial 1,040,000 m³ to 832,516.85 m³ over a 33-year period, representing a reduction of 19.95%. Additionally, the effective storage capacity slightly decreased from 8,667,000 m³ to 8,666,000.01 m³, corresponding to a minimal reduction of approximately 0.0115%. The sediment deposition pattern identified in the Tugu Dam reservoir through HEC-RAS modeling is uniform, with a total sediment accumulation volume of 207,483.14 m³.